The Role of Sustainable Innovation in Enhancing MSME Resilience as a Driver of Community Empowerment - Sari, Ade Risna; Suparwata, Dewa Oka; Yani, Ahmad (PT. LITERASI SAINS NUSANTARA, 2024)
Sustainable innovation has become an important topic across various business sectors, particularly in micro, small, and medium enterprises (MSMEs). For MSMEs, sustainable innovation is crucial for surviving competition and creating significant added value for society. This study focuses on how sustainable innovation can enhance the resilience of MSMEs in fulfilling their role as a driver of community empowerment. The research employs a literature review method with a qualitative approach and descriptive analysis. Data for this study were sourced from the Google Scholar database, covering the period from 2014 to 2024. The findings indicate that sustainable innovation plays a significant role in improving the resilience of MSMEs as a driver of community empowerment. MSMEs are better equipped to face various challenges and contribute to social and economic development in their communities by adopting environmentally friendly, operationally efficient, and market-relevant innovations. Case studies such as Batik Jogja Gallery, Warung Pintar, Kampung Marketer, and EcoBali Recycling illustrate that MSMEs that successfully innovate sustainably can generate enduring economic, social, and environmental value. However, this success heavily relies on support from various stakeholders, particularly regarding access to technology, financing, and favorable regulations.